Paper eaudiobook Paging through history. - Kurlansky, Mark (Recorded Books, 2016)
From the New York Times best-selling author of Cod and Salt, a definitive history of paper and the astonishing ways it has shaped today's world. Paper is one of the simplest and most essential pieces of human technology. For the past two millennia, the ability to produce it in ever more efficient ways has supported the proliferation of literacy, media, religion, education, commerce, and art; it has formed the foundation of civilizations, promoting revolutions and restoring stability. By tracing paper's evolution from antiquity to the present, with an emphasis on the contributions made in Asia and the Middle East, Mark Kurlansky challenges common assumptions about technology's influence, affirming that paper is here to stay. Paper will be the commodity history that guides us forward in the twenty-first century and illuminates our times. "[An] historical journey well worth the ride. [Kurlansky] has a deep instinct for telling detail, which he combines with a disarmingly fun narrative style."—Los Angeles Times